Rethinking tube feeding in palliative care: Impact on pneumonia, depression, and mortality in patients with dysphagia and life-limiting illness - Jennifer Hanners Gutierrez; Kelly Klein; Milan Bimali; Jessica Sanders (PLoS ONE, 2025)
Introduction Tube feeding continues to be recommended for nutrition when a patient has dysphagia amid life-limiting illness. Tube feeding is frequently claimed to be a safer alternative to oral feeding. Oral feeding, including careful hand feeding, has emerged as a viable and evidence-based alternative for patients who desire nutrition at the end of life but have trouble swallowing. There is a critical need to determine the best option for a feeding route at the end of life. This novel, pilot, prospective study was conducted to contribute toward that need. This is the first study of its kind. Aims Researchers aimed to investigate the impact of feeding route (oral or tube) on patient outcomes, contributing to scientific knowledge as related to nutritional decision-making when patients are critically or terminally ill, desiring nutrition, and diagnosed with dysphagia. Methods Participants (N = 65) were admitted to a tertiary center, diagnosed with dysphagia and life-limiting illness, and treated by Palliative or Family Medicine. Data were collected as related to demographic (age, sex, race, ethnicity) and clinical statistics (mortality risk/severity of illness, primary diagnoses, patient outcomes [pneumonia, depression, and mortality], and feeding route [oral and tube]). Logistic regression modeling (unadjusted and adjusted by mortality risk and age) and propensity score matching were used to analyze data. Results Results indicated a greater likelihood of negative clinical outcomes as related to tube versus oral feeding. Findings challenge default use of tube feeding as a safer alternative for nutrition. Specifically, results revealed tube feeding to be significantly (p < 0.001) associated with increased risk of pneumonia (adjusted OR = 19.28, p < 0.01) and significantly (p < 0.001) associated with depression (adjusted OR = 17.25, p < 0.01), with mortality also trending higher (adjusted OR = 2.78, p = 0.147). Moreover, a composite outcome analysis (pneumonia, depression, or mortality) revealed impressively greater odds of an adverse event occurring due to tube versus oral feeding (adjusted OR = 55.64, p < 0.01), underscoring the need to consider further research and a possible paradigm shift in nutritional decision-making for palliative care patients. The propensity score analysis yielded balanced, matched groups (n = 30), 15 participants who were oral-fed and 15 who were tube-fed. Results also revealed significantly higher rates of pneumonia (p < 0.001) and depression (p = 0.035) in participants who received tube versus oral feeding. Again, mortality trended higher but significant results were not achieved. Clinical implications These results have substantial clinical implications. Results support reconsidering routine tube feeding in favor of individualized, patient-centered approaches that prioritize quality of life and informed decision-making. This pilot study contributes to ongoing discussions about evidence-based palliative care and has the potential to influence guidelines on feeding practices for terminally-ill patients.